Gene replacement therapy in a schwannoma mouse model of neurofibromatosis type 2 - Prabhakar, Shilpa; Beauchamp, Roberta L.; Cheah, Pike See; Yoshinaga, Akiko; Haidar, Edwina Abou; Lule, Sevda; Mani, Gayathri; Maalouf, Katia; Stemmer-Rachamimov, Anat; Jung, David H.; Welling, D. Bradley; Giovannini, Marco; et al. (Cell Press, 2022)
Loss of function of the neurofibromatosis type 2 (NF2) tumor suppressor gene leads to the formation of schwannomas, meningiomas, and ependymomas, comprising ∼50% of all sporadic cases of primary nervous system tumors. NF2 syndrome is an autosomal dominant condition, with bi-allelic inactivation of germline and somatic alleles resulting in loss of function of the encoded protein merlin and activation of mammalian target of rapamycin (mTOR) pathway signaling in NF2-deficient cells. Here we describe a gene replacement approach through direct intratumoral injection of an adeno-associated virus vector expressing merlin in a novel human schwannoma model in nude mice. In culture, the introduction of an AAV1 vector encoding merlin into CRISPR-modified human NF2-null arachnoidal cells (ACs) or Schwann cells (SCs) was associated with decreased size and mTORC1 pathway activation consistent with restored merlin activity. In vivo, a single injection of AAV1-merlin directly into human NF2-null SC-derived tumors growing in the sciatic nerve of nude mice led to regression of tumors over a 10-week period, associated with a decrease in dividing cells and an increase in apoptosis, in comparison with vehicle. These studies establish that merlin re-expression via gene replacement in NF2-null schwannomas is sufficient to cause tumor regression, thereby potentially providing an effective treatment for NF2.